2015
DOI: 10.1002/jcsm.12077
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K11/GDF15 axis is a critical driver of cancer cachexia

Abstract: BackgroundCancer associated cachexia affects the majority of cancer patients during the course of the disease and thought to be directly responsible for about a quarter of all cancer deaths. Current evidence suggests that a pro‐inflammatory state may be associated with this syndrome although the molecular mechanisms responsible for the development of cachexia are poorly understood. The purpose of this work was the identification of key drivers of cancer cachexia that could provide a potential point of interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
181
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(191 citation statements)
references
References 48 publications
9
181
1
Order By: Relevance
“…With respect to protein-energy wasting pathways, GDF15 acts directly upon the hypothalamus to reduce food intake and energy expenditure [20]. In animal models, GDF15 administration has been shown to lead to satiety and weight reduction, which has been reversed or prevented by the administration of anti-GDF15 neutralizing antibodies [20,26,42]. Notably, in the sensitivity analyses we found that the relationship between higher GDF15 levels and higher mortality risk persisted following adjustment for body size (i.e., BMI) and protein intake (i.e., nPCR), suggesting that cardiovascular pathways may be implicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to protein-energy wasting pathways, GDF15 acts directly upon the hypothalamus to reduce food intake and energy expenditure [20]. In animal models, GDF15 administration has been shown to lead to satiety and weight reduction, which has been reversed or prevented by the administration of anti-GDF15 neutralizing antibodies [20,26,42]. Notably, in the sensitivity analyses we found that the relationship between higher GDF15 levels and higher mortality risk persisted following adjustment for body size (i.e., BMI) and protein intake (i.e., nPCR), suggesting that cardiovascular pathways may be implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in cancer-associated cachexia, circulating GDF15 levels correlate with weight loss, lower lean body and fat mass, weaker handgrip strength, and worse survival [21]. These findings bear particular relevance to the hemodialysis population, in whom weight loss and protein-energy wasting are among the most potent predictors of mortality, including cardiovascular death [22,23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Circulating mediators of inflammation implicated in cancer-induced muscle wasting include members of the TNF, IL-6, IFN, and IL-2 families of cytokines, although the only factors thus far consistently correlated with cachexia overall are IL-6, Activin A and Growth Differentiation Factor (GDF)-15, the latter two members of the Transforming Growth Factor-β superfamily [118121]. The relationship is a general one, however, with the concentrations of these factors highly heterogeneous across patients.…”
Section: Systemic Inflammation In Cancer Cachexiamentioning
confidence: 99%
“…Careful and numerous genetic studies demonstrate that endogenous STAT3 plays essential, protective roles for cardiac size and function [118]. Male mice with cardiomyocte-specific deletion of STAT3 develop heart failure, while female mice develop post-partum cardiac myopathy.…”
Section: 0 Stat3 Outside Muscle In Cachexiamentioning
confidence: 99%
“…GDF15 is a hormone known to affect appetite, and is highly expressed in placental trophoblasts and decidual stromal cells. High GDF15 is a key driver in cancer cachexia,12 which is characterised by symptoms similar to HG: nausea, weight loss, and muscle wasting. Further research replicating these findings and establishing causality is needed.…”
Section: What Causes It?mentioning
confidence: 99%